Trimetazidine Protects Cardiomyocytes Against Hypoxia/Reoxygenation Injury by Promoting AMP-activated Protein Kinase–dependent Autophagic Flux. Issue 6 (June 2017) - Zhong, Yongkang; Zhong, Peiyao; He, Shangfei; Zhang, Ya; Tang, Lu; Ling, Yuanna; Fu, Shanshan; Tang, Ying; Yang, Pingzhen; Luo, Tao; Chen, Baihe; Chen, Aihua; et al.
Abstract : Abstract: Trimetazidine (TMZ), a metabolic agent, may protect against myocardial ischemia/reperfusion injury. Because of the critical role of autophagy in cardioprotection, we aimed to evaluate whether autophagy was involved in TMZ-induced protection during hypoxia/reoxygenation (H/R). Neonatal rat cardiomyocytes were subjected to H/R injury, and they were divided into 7 groups: control, control+TMZ, control+chloroquine (Cq)/compound C (com C), H/R, H/R+TMZ, H/R+Cq/com C, and H/R+TMZ+Cq/com C. Autophagic flux was primarily assessed by Western blot and tandem fluorescent mRFP-GFP-LC3. Assays for MTS, terminal deoxynucleotidyl transferase–mediated dUTP nick end labeling, and lactate dehydrogenase release were performed to assess cell injury. Our results showed that TMZ pretreatment had a cardioprotective effect against H/R injury. The H/R+TMZ group had an increased ratio of LC3-II to LC3-I and increased autophagic flux (degradation of p62 and increases in autophagosomes and autolysosomes). TMZ also reduced apoptosis and enhanced cell survival while inducing autophagy. Correspondingly, autophagy inhibition with Cq blocked this protective effect. Furthermore, TMZ-induced enhancement of autophagy could be related to increased AMP-activated protein kinase (AMPK) phosphorylation and decreased Mammalian target of rapamycin (mTOR) phosphorylation, which was abolished by an AMPK-specific inhibitor (com C). Our data provide evidence that TMZ pretreatment protects against H/R injury by promoting autophagic flux through the AMPK signaling pathway.